First report of Diaporthe tulliensis causing leaf spot on Millettia speciosa in China - Pan, Jie-Ming (Plant disease, 2024)
Millettia speciosa Champ, renowned for its diverse applications in traditional medicine, is extensively cultivated in the Guangxi region of China, spanning roughly 5,973 hectares. In July 2021, a plantation in Yulin, Guangxi, China (22°64'N; 110°29'E), exhibited severe leaf spot disease on M. speciosa. Notably, a 46,690 square meters area had over 40% leaf spot incidence. Initially, symptoms appeared as small, circular, pale-yellow lesions on the leaves, then turned into irregular, dark brown spots with yellow halos, leading to the wilt and defoliation of leaves. To identify the responsible pathogen, a total of five symptomatic leaves were collected and sterilized systematically. Small tissue segments (5×5 mm) from lesion peripheries were aseptically excised, then surface sterilized with 75% ethanol for 10 s, and 1% sodium hypochlorite (NaClO) for 3 min. Following this, the sterilized tissues were triple-rinsed with sterile water and cultured on potato dextrose agar (PDA) at 28 °C in the dark for 7 d. A total of seven isolates were obtained through single-spore isolation, and one representative isolate, N2-3, was selected for further analysis. After 7 d of incubation, colonies displayed flat, white, and extensively branched aerial hyphae. Over time, the reverse side of the colony changed from white to yellowish-white. The pycnidia were black with conidial droplets ranging from cream to pale yellow exuding from their ostioles. The α-conidia were one-celled, hyaline, ovoid to cylindrical, typically with one or two droplets, 2.6 to 5.9 ×1.4 to 3.9 μm (n=50). These morphological traits align with those of the genus Diaporthe, as reported by Li et al. (2022) and Crous et al. (2015). To identify the species, isolate N2-3 underwent sequencing of the internal transcribed spacer (ITS), β-tubulin (BT), and translation elongation factor 1 alpha (EF1-α) sections (Huang et al. 2021). Obtained sequences of ITS, BT and EF1-α (Genebank accessions nos. OR600532, OR662169 and OR662168) displayed a 99% similarity to Diaporthe tulliensis (Genebank accessions nos. OP219651, ON932382, OL412437, respectively). Based on the concatenated ITS, BT and EF1-α, a neighbor-joining phylogenetic analyses using MEGA7.0 clustered with D. tulliensis. Therefore, the fungus was identified as D. tulliensis (teleomorph name) based on morphological and molecular features. A pathogenicity test was conducted on 1-year-old M. speciosa seedlings by gently abrading healthy leaves with sterilized toothpicks to create superficial wounds. Wounded leaves were then inoculated with 5 mm diameter mycelial plugs, while control seedlings received PDA plugs. Three leaves per plant and five plants per treatment were selected for assessment. All seedlings were kept in a controlled greenhouse (12/12h light/dark, 25 ± 2 °C, 90% humidity). After 7 d, the inoculated leaves showed symptoms like those in the field, while control plants remained healthy. The fungus was consistently reisolated from the infected leaves, satisfying Koch's postulates. Notably, D. tulliensis has caused Boston ivy leaf spot, bodhi tree leaf spot, cacao pod rot, and jasmine stem canker (Huang et al. 2021; Li et al. 2022; Serrato-Diaz et al. 2022; Hsu et al. 2023). This discovery is significant as it marks the first report of Diaporthe tulliensis causing leaf spot on Millettia speciossa in China, which has direct implications for the development of diagnostic tools and research into potential disease management strategies